Silica Supraparticles with Self‐Oscillatory Vertical Propulsion: Mechanism & Theoretical Description. (14th June 2022) - Kim, Hyung‐Ju; Sperling, Marcel; Velev, Orlin D.; Gradzielski, Michael
Abstract: A novel type of mm‐sized silica‐based self‐propelling supraparticles displaying buoyancy‐driven homogeneous vertical oscillatory motion using aqueous hydrogen peroxide (H2 O2 ) as chemical fuel is presented. The supraparticles are prepared via a robust droplet templating technique by drying colloidal suspension droplets containing silica microspheres and catalytic Fe3 O4 @Pt decorated nanoparticles on a superhydrophobic Cu–Ag surface. Oxygen gas originating from Pt catalyzed decomposition of H2 O2 is released and gathered onto the hydrophobic supraparticle surface. This causes buoyancy and uplift of the particle to the surface, where the oxygen bubble is released and the particle descents again, leading to an oscillating process in a very regular fashion. The mechanism of this process is characterized and analyzed here quantitatively by a balance of the gravitational and buoyant forces. The theoretical model of particle movement describes how the particle oscillation period depends on the H2 O2 concentration. This novel type of self‐propelling particles could find potential applications in mixing and catalysis, especially due to the high regularity of their periodic movement. Abstract : The dynamics of silica supraparticles with self‐oscillatory vertical propulsion by decomposition of H2 O2 in aqueous media are described. The prepared mm‐sized self‐propelling supraparticles with a catalyst can perform oscillating elevator motion. A model correlating oscillation motion and H2 O2 concentration are derived by balancing buoyancy against gravity while considering solvent density, reaction kinetics, friction, and oxygen collected on the supraparticle structure.